Effect of tree shape and green wood properties on tree stability - Lim, Starsky (2014)
Six common urban species found in Singapore with distinct tree shapes, i.e. Samanea Saman (“Rain tree”), Khaya Senegalisis (“African mahogany”), Peltophorum Pterocarpum (“Yellow flame”), Pterocarpus Indicus (“Angsana”), Eugenia Grandis (“Sea apple”) and Tabebuia Rosea (“Trumpet tree”) were selected as the subjects of study. Green wood properties of tree branches such as modulus of rupture (MOR) and modulus of elasticity at point of rupture (MOEr) were obtained from field tests using a portable 3-point bending test machine. A new surveying method and nomenclature were developed for fast and acceptable readings of the tree. Two softwares (AutoCAD and ANSYS) were used to model the tree shape using the coordinates obtained from the surveying method and the geometries were obtained. These values were then used to study the tree stability with regards to uprooting failure mode. A ratio of Vwc/V40 of 0.58 and 1.29 was recorded for the Rain Tree and Sea Apple respectively. A ratio of Vwc/V25 of 0.93 and 2.06 was recorded for the Rain Tree and Sea Apple respectively.